2023
DOI: 10.1101/2023.07.04.547690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus Serum Stimulation of Human Intestinal Organoids Induces Changes in Goblet Cell Differentiation and Mitochondrial Fitness

Inga Viktoria Hensel,
Szabolcs Éliás,
Michelle Steinhauer
et al.

Abstract: Human intestinal epithelial cells are the interface between potentially harmful luminal content and basally residing immune cells. Their role is not only nutrient absorption but also the formation of a tight monolayer that constantly secrets mucus creating a multi-layered protective barrier. Alterations in this barrier can lead to increased gut permeability which is frequently seen in individuals with chronic extraintestinal autoimmune diseases, such as Systemic Lupus Erythematosus (SLE). Despite recent advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 144 publications
0
1
0
Order By: Relevance
“…Hensel et al support this idea. In a study of SLE patients, they found a significant decrease in the intensity of MUC2 immunofluorescence staining, which indicates an alteration of the function of goblet cells or the secreted mucus [33]. By treating the dysbiosis of Bifidobacterium in SLE patients, there is a potential to restore goblet cell function and mucus secretion and offer therapeutic relief for the intestinal dysfunctions these patients may be experiencing.…”
Section: Negatively Associated Bacteria With Slementioning
confidence: 99%
“…Hensel et al support this idea. In a study of SLE patients, they found a significant decrease in the intensity of MUC2 immunofluorescence staining, which indicates an alteration of the function of goblet cells or the secreted mucus [33]. By treating the dysbiosis of Bifidobacterium in SLE patients, there is a potential to restore goblet cell function and mucus secretion and offer therapeutic relief for the intestinal dysfunctions these patients may be experiencing.…”
Section: Negatively Associated Bacteria With Slementioning
confidence: 99%